Edukasi Digital Marketing Sebagai Upaya Meningkatkan Jiwa Entrepreneurship Pada Komunitas Genpreneur Muda Di Kampung Tengah - Rahmawati Rahmawati; Zubaidah Assyifa; Mifta Hasda; Rio Panji Saputra; Hairullah Efendi (Journal of Community Sustainability, 2026)
This community service activity is aimed at the Young GenPreneur community as an effort to foster an entrepreneurial spirit through the use of digital marketing. The goal was to determine participants' level of understanding of digital marketing while simultaneously improving their entrepreneurial knowledge and skills. The methods used included counseling, presentations, and interactive discussions. The results of the activity indicate that the program was implemented well and according to plan. Participants experienced an increased understanding of the basic concepts of digital marketing and Islamic business, as well as their ability to utilize social media as a marketing tool. Furthermore, this activity successfully improved participants' practical skills, motivation, and confidence in entrepreneurship. A better understanding of digital marketing strategies also opened up broader market opportunities for participants. This program is expected to foster a sustainable entrepreneurial spirit, encourage business independence, and create a productive and competitive community. Thus, participants can contribute to economic development at the local, national, and international levels.